INTEGRATED SERVICE CENTER FOR THE EMPOWERMENT OF WOMEN AND CHILDREN (P2TP2A) FOR THE PROTECTION OF VICTIMS OF SEXUAL VIOLENCE - Aprillio Poppy Belladonna; HIdayah, Yayuk; Neneng Tripuspita (Journal of Innovation Research and Knowledge, 2023)
A number of efforts to protect victims of sexual violence are efforts to fulfill information and needs in the fields of education, health, economics, politics, law, protection and prevention of acts of violence and trafficking of women and children. The presence of the Integrated Service Center for the Empowerment of Women and Children (P2TP2A) has become a place to provide all forms of protection for victims of sexual violence. This study aimed to describe how P2TP2A in West Bandung Regency could play a role to protect victims of sexual violence. The study was qualitative research with case study as method. The study was conducted in the Integrated Service Center for Women and Children Empowerment (P2TP2A), located in West Bandung Regency, Indonesia. The data were collected using interview, observation, documentation, and literature studies, while the analysis was conducted using the analysis model of Miles and Huberman, namely data reduction, data display, and conclusion drawing/verification. This study resulted that P2TP2A provided prevention, treatment and rehabilitation for victims of sexual violence. In its preventive effort, P2TP2A conducted campaigns, counseling and socialization regarding the dangers of sexual violence. In the handling efforts, P2TP2A received cases, facilitating psychological services, health and legal assistance. Meanwhile, in its rehabilitative efforts, P2TP2A provided safe-house protection and technological guidance to each task force in West Bandung P2TP2A. From the results, this study concluded that P2TP2A is the front guard in providing protection for victims of sexual violence.